TRANSCRIPTIONAL RESPONSE OF THE MULTIDRUG RESISTANT Staphylococcus aureus FOLLOWING FS-1 EXPOSURE - Korotetskiy , I.S.; Shilov , S.V.; Shvidko , S.V.; Jumagaziyeva , A.B.; Suldina , N.A.; Korotetskaya , N.V.; Ilin , A.I.; Reva , O.N. (Eurasian Journal of Applied Biotechnology, 2017)
The aim of this study was to evaluate transcriptional regulation in a model multidrug resistant Staphylococcus aureus (MRSA) culture, S. aureus ATCC® BAA-39™, after exposure to a new antibacterial drug, FS-1. Growth media were supplemented with FS-1 at the end of the lag phase and in the middle of the exponential growth phase. To investigate the immediate effects of the iodine-containing antibacterial complex FS-1, 24 RNA samples were obtained 5 min after exposure to the drug.RNA sequencing revealed substantial changes in gene expression in the lag phase and, to a lesser degree, in the exponential growth phase. Analysis of the regulated genes suggested that FS-1 primarily targeted microbial cell wall proteins. The effect of FS-1 on S. aureus gene expression was similar, but not identical, to differential gene regulation profiles caused by several cell wall-disrupting antibiotics including bacitracin, D-cycloserine, and oxacillin. However, the gene regulation profiles were not completely congruent, suggesting that FS-1 displays a significant level of antimicrobial activity specificity. Therefore, it is possible that combining FS-1 with other anti-staphylococcal antibiotics will result in a cumulative synergetic effect.